Protestas relacionadas con la minería en Colombia 2000-2015 - Martha Cecilia García Velandia (Berlin, 2017)
– The global commodity boom are accompanied by the rise of social protest in Colombia. The protestors claim the pollution of the environment, the bad social standards and working conditions and the unfair distribution of the benefits from the raw material boom. The social protest is diverse and manifold. Their character depends on who is protesting, on the corporate reactions and strategies, the mode and the actors (corporations, artisanal miners, ilegal miners etc.) of extraction. The paper presents and analyzes a database on social protests against miming in Colombia between 2000 and 2015. The Data were collected by the centre of investigation and popular educacion/ program for peace (Centro de Investigación y Educación Popular/ Programa por la paz). The Paper systemizes and interprets the database and exemplifies them with four cases of protests against gold and coal mining.
urn:nbn:de:kobv:188-refubium-25015-8
Keywords: 330; Colombia; mining; social protest; Kolumbien; Bergbau; sozialer Protest